Nepal Country Climate and Development Report - World Bank Group (World Bank, Washington, DC, 2022)
This Country Climate and Development Report (CCDR) identifies ways that Nepal can achieve its overall development objectives while fostering its strategic ambition to transition to a greener, more resilient, and inclusive development pathway. This report is organized as follows: Chapter 1 captures the current situation in the country with respect to climate impacts and risks, emission sources, and opportunities for integrated climate change adaptation and mitigation. Chapter 2 describes the government’s response, through sectoral and economywide commitments, laws, and regulations. Chapter 3 assesses the impacts of climate change on the macroeconomy and road transport systems, given their critical role to connectivity. It also analyzes the links between climate change and air pollution, poverty, health, social inclusion, and community resilience. Chapter 4 presents pathways to transition to resilience, looking at integrated management of landscape systems comprising water, agriculture, and forests as well as strengthening climate and disaster risk management governance. Chapter 5 analyzes pathways to transition to decarbonization, primarily the potential for hydropower expansion domestically and in the region. It also looks at transport and urban opportunities to reduce emissions while enhancing resilience and adaptation co-benefits. Chapter 6 discusses how to scale up financing for resilience, hydropower, and other opportunities, given the limitations of the country’s fiscal space. Chapter 7 presents a prioritization framework for the most transformational climate action with seven ‘policy packages’—one for each priority transition and each key enabler—that contain specific recommendations for how to move from analysis to action.